2008
DOI: 10.1159/000173004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Primary Amphetamine Users in Sweden: A Criminal Justice Population Examined with the Addiction Severity Index

Abstract: Background/Aims: Characteristics of primary amphetamine, heroin and cocaine users were compared in a criminal justice population. Methods: 7,085 clients with suspected or reported substance use were studied using the Addiction Severity Index. Variables separating amphetamine, heroin and cocaine users were analyzed in stepwise logistic regression. Results: There were considerably more primary amphetamine users (n = 1,396) than heroin (n = 392) and cocaine (n = 119) users. Amphetamine users were older, a more ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 92 publications
(73 reference statements)
1
22
1
Order By: Relevance
“…One explanation to as why individuals with a diagnosis of amphetamine and/or cocaine use disorder distinguish themselves from other SUD subtypes might be associated with the often unstable living conditions among active amphetamine users (42). Socializing with substance using peers, low rates of permanent employment and high prevalence of criminal activities are all factors known to negatively impact treatment outcome and adherence (43).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation to as why individuals with a diagnosis of amphetamine and/or cocaine use disorder distinguish themselves from other SUD subtypes might be associated with the often unstable living conditions among active amphetamine users (42). Socializing with substance using peers, low rates of permanent employment and high prevalence of criminal activities are all factors known to negatively impact treatment outcome and adherence (43).…”
Section: Discussionmentioning
confidence: 99%
“…This is the cohort assessed in a previous paper describing how baseline characteristics separate this group from primary users of other major substances of abuse (heroin and cocaine) and with low rates of overlap of recent use with these substances (Hakansson et al, 2009). As potential predictors of death, we included variables describing substance use, physical illness, psychiatric problems (previously or during 30 days prior to incarceration), and demographic data (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…In the Swedish setting assessed here, amphetamine has been the predominating drug in heavy drug users (Byqvist, 2006) and the most common primary drug among criminal justice clients (Hakansson, Schlyter, & Berglund, 2009). Internationally, illicit drug abuse is common among criminals: a recent review reported prevalence of substance use disorders ranging between 30% and 60% in female prisoners and 10% and 48% in male prisoners (Fazel, Bains, & Doll, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, amphetamine misuse appeared early and intravenous amphetamine use has been a dominant feature of drug use in Sweden in contrast to many countries (Håkansson, Schlyter, & Berglund, 2009). According to Lenke and Olsson (1999), the drug problem in Sweden began after the Second World War with an extensive use of oral amphetamines.…”
Section: A "Drugs As a Good Enemy" Discoursementioning
confidence: 99%